Precipitation contributes to plant height, but not reproductive effort, for western prairie fringed orchid (Platanthera praeclara Sheviak & Bowles): Evidence from herbarium records. Issue 17 (9th August 2020) - Biederman, Lori A.; Weldon, Sydney M.; Anderson, Derek S.; Leoschke, Mark J.
Abstract: The western fringed prairie orchid (WFPO) is a rare plant found in mesic to wet tallgrass prairies in the Great Plains and Midwest regions of the United States. The size of WFPO populations varies considerably from year to year, and studies have suggested that population size is dependent on precipitation during critical periods in the plant's annual development. We hypothesized that plant height and reproductive effort would also be controlled by precipitation, either during these periods or over a broader period. We acquired available images of WFPO from 21 herbaria, and of these 141 individual plants had information adequate for analysis, although some population/year combinations were represented multiple times. For each specimen, we measured plant height (cm) and reproductive effort (as measured by total flower and bud count). We used bootstrapped linear regression, randomly selecting one individual from each population/year combination, to compare precipitation models, both during critical periods and the various summaries. We found that precipitation during the phenologically critical periods was a poor predictor of plant height and reproductive effort. Of the broader precipitation variables, accumulated precipitation from January 1 to collection date best described plant height. We also used correlations to detect a relationship among the variables WFPO height, reproductive effort, precipitation, latitude, and year of collection. Year of specimen collection was negatively correlated with WFPO plant height and accumulated precipitation, suggesting that both have declined in more recent years. Negative correlations with latitude also suggest height and precipitation decrease in the northern part of WFPO's range. Reproductive effort was not related to tested precipitation variables; however, it was weakly correlated with plant height. Although the results are limited, this study leverages available data and makes inferences on WFPO biology over broad ranges of time (1894–2012) and latitude (37.5°–49.9°). Abstract : Using herbarium specimens from a broad range of time (1894–2012) and latitude (37.5°–49.9°), we consider the influence of precipitation on the height and reproductive effort for Platanthera praeclara (western prairie fringed orchid). We found that precipitation during phenologically significant periods was a poor predictor of plant height, but accumulated precipitation from 1 January to collection date best described plant height. Reproductive effort, as measured by flower and bud number, was not affected by environmental conditions and only weakly correlated with plant height.